The Influence of Poverty Levels, GRDP Per Capita and Number of Schools on School Enrollment Rates in West Nusa Tenggara Province - M. Daffa’ Arkaanjani (Tinta Emas Institute, 2023)
This research aims to analyze the influence of poverty level, GRDP per capita, and number of schools on school participation rates in West Nusa Tenggara Province. This type of research is quantitative descriptive. The data used is secondary data taken from the Central Statistics Agency (BPS) of West Nusa Tenggara Province. The data collection technique is documentation. The analytical method used in this research is the Ordinary Least Square (OLS) method. Where in this method Ordinary Least Square is to test the influence of two or more independent variables on one dependent variable. The results of the analysis show that the variables Poverty Level, GRDP Per Capita, and Number of Schools together (simultaneously) have a positive and significant effect on the Participation Rate Schools in West Nusa Tenggara Province. Individually (partially), the Poverty Level and GRDP Per Capita variables have a positive and significant effect on the School Enrollment Rate, while the Number of Schools variable has a negative and insignificant effect on the School Enrollment Rate in West Nusa Tenggara Province. From the results of the determinant test (R2), the R-Squared value is 0.890436. This means that the independent variable is able to explain variations in the dependent variable, namely labor absorption in the small and medium industrial sector in West Nusa Tenggara Province of 89 percent, while the remaining 11 percent can be explained by other factors outside the model in this research.